Chapter 10 Troubles with the Orthogonality Thesis - Hvorecký, Juraj (Taylor & Francis, 2024)
This chapter evaluates some basic assumptions behind the "dual" theories of phenomenal consciousness and finds them problematic for at least some examples of conscious episodes. Because the dual theories claim to be universalist in nature, even small number of counterexamples damages their status. I will present evidence, both empirical and conceptual, that demonstrates untenability of the dualist assumptions that conscious phenomenality and its unconscious counterpart possess essentially the same qualities. In doing so, I will primarily attack the claim that is shared by many dual theorists that the procedure responsible for bringing phenomenal content into consciousness serves this sole function and does not influence phenomenal qualities of content. I use the term orthogonality, first introduced in Vosgerau et al. (2008), as a convenient shortcut for the conception in which consciousness and content come unproblematically apart. I will conclude by hinting at an alternative proposal that explains emergence of conscious phenomenality as a single step operation.